Nanomedicine and regulatory science: the challenges in Africa - Nyazema, N. Z.; Chanyandura, J. T.; Kumar, P. O. (Frontiers in Biomaterials Science, 2023)
The integrated approach in the development of nanotechnology is allowing introduction into multiple fields including pharmaceutical research in which there are now a number of medicines containing nano-materials or at least nano-based claims. As a result of increasing research in nanotechnology, pre-existing medicines have been reformulated and new ones. This has brought challenges for the current regulatory frameworks in Europe and the United States. These regulatory agencies are known to be stringent because not only do they have the human capacity and skills, but also conducive policies and the landscape to do so unlike in most African countries. Because the EMA and FDA have embraced regulatory science (RS) as a means of proactive analysis of regulatory principles while involving them along continuity of scientific progress, it is going to be easy to deal with nanomedicine challenges. African countries currently do not have a harmonized regulatory framework because different national regulatory authorities are at different levels of development. The pharmaceutical sector in Africa is facing many challenges which include non-existence of research and development partnership between industry, universities and research institutions to foster nanomedicine development. Now that the African Medicine Agency, AMA is in place, Africa should see the rapid implementation of AU Model Law on the regulation of medical products which will assist in putting in place capacity building programmes in nanomedicine RS.